Estudos dos metabólitos secundários de Exophiala spinífera em diferentes condições de cocultivos com Leucoagaricus gongylophorus para o controle das formigas cortadeiras - Zandonai, Dorai Periotto (2022)
STUDIES OF SECONDARY METABOLITES UNDER DIFFERENT COCULTIVATION CONDITIONS BETWEEN Exophiala spinifera and Leucoagaricus gongylophorus FOR THE CONTROL OF LEAF-CUTTING ANT. Leaf-cutting ants are among the main pests of Brazilian agriculture, causing significant damage to agribusiness. Cultural, chemical and biological control strategies were specially developed to reduce costs and the amount of insecticides applied. The chemistry of natural products appears as an important ally to study the metabolic profile of plants and microorganisms in order to isolate and/or identify the secondary metabolites produced with specific biological activities and providing less impact to the environment. Co-cultivation of fungi has been described as a promising strategy to induce the production of new metabolites through interactions between different strains. Therefore, this work aimed to evaluate co-culture conditions between the mutualistic fungus Leucoagaricus gongylophorus responsible to produce enzymes that degrade foliar polysaccharides into assimilable nutrients for ants together with the black yeast Exophiala spinifera (Herpotrichiellaceae), isolated from the ant male of Atta laevigata, (Formicidae). In addition, we sought to carry out the cultivation of black yeast, to isolate and identify new metabolites with biological activity in the control of leaf-cutting ants. The growth conditions of the co-cultures and the cultivation of pure strains were evaluated in this study, determining the best culture medium and the time of production of the metabolites through the study of the growth kinetics. To study the metabolites induced in fungal interactions, Nuclear Magnetic Resonance and High-Resolution Mass Spectrometry analyses were performed associated with the application of metabolomics tools and the Global Natural Products Social Molecular Networking (GNPS) platform in strains of pure cultures and their cocultures. This set of techniques, made it possible to identify metabolites highlighted in co-cultures. Among the results, the isolation of an exophilic acid derivative (2-hydroxy-4-[4-hydroxy-2-nonyl-6-[3,4,5-trihydroxy-6-(hydroxymethyl)oxan-2-yl]oxybenzoyl]oxy-6-nonylbenzoic acid),(C40H58O17). Agar diffusion assays were performed with co-culture (halo de inhibition 24,5 mm) and pure culture of the crude extract Exophiala spinifera (halo de inhibition 24,8 mm) and isolated compound (P7) (halo de inhibition 25,8 mm) showed inhibition for L. gongylophorus. Bioassays were also performed with the enzyme Acetylcholinesterase (AChE) extracted from Electrophorus electricus and AChE the leaf-cutting ant Atta sexdens. They were tested with crude extract of Exophiala spinifera (I % 75.04 ± 0.099) and with the compound isolated (P7) from black yeast monocultures (I % 68.45 ± 0.020), which showed inhibition. The isolated compound P7 and the crude extract of Exophiala spinifera was evaluated for the inhibition of Acetylcholinesterase enzyme in disposable microelectrodes, showing inhibition. In this context, compounds biosynthesized by the microorganism Exophiala spinifera can be natural alternative for the control of leaf-cutting ants.